Difference in inflammatory cytokine production by mononuclear cells from obese and non‐obese schizophrenic patients. (28th January 2015) - Sirota, P.; Hadi, E.; Djaldetti, M.; Bessler, H.
Abstract : Objective: Schizophrenic patients have an increased risk for obesity compared with the general population. Evidence suggests the existence of an inflammatory process in the etiology of both obesity and schizophrenia. Our study compares in vitro secretion of inflammatory cytokines by peripheral blood mononuclear cells (PBMC) obtained from obese and non‐obese schizophrenic patients. Method: Mononuclear cells were isolated from 20 obese (BMI >27) and 20 non‐obese (BMI <24) schizophrenic in‐patients. The levels of TNF‐α, IL‐1β, IL‐6, IL‐1ra, IL‐10 or IL‐2 and IFN‐γ in the supernatants of stimulated PBMC, as well as leptin and adiponectin serum values were evaluated. Results: Peripheral blood mononuclear cells from patients in the obese group showed a significantly increased TNF‐α and IL‐1β production, whereas the release of IL‐1ra was decreased as compared with the non‐obese group. In the obese group, the serum concentration of leptin was significantly higher and that of adiponectin was significantly lower. The results of the remaining cytokines did not differ between the two groups. Conclusion: Our study indicates the existence of a difference between obese and non‐obese schizophrenic subjects as for inflammatory cytokine production and serum leptin and adiponectin levels, suggesting a 'subclinical inflammatory state' in obese schizophrenic patients that may contribute to a predisposition to inflammation and infections.